TOWARDS A CULTURAL POLITICAL ECONOMY: Staging an Encounter between Marx, Gramsci, and Foucault - Sum, Ngai-Ling (Politeia, 2019)
This article elaborates one possible development of Marx’s legacy 200 years after his birth. It responds to the influence of post-structuralism and its related ‘cultural turn’ on academic Marxist analyses by examining the material and discursive dimensions of changing social relations in capitalist social formations. In this context, it proposes a cultural political economy approach to bridge the theoretical divide between constructivism and structuralism. It suggests that, given his long-standing interests in language and semiosis as key aspects of the critique of economic, political, and social life, Marx can fruitfully be read as a proto-cultural political economist. It is further suggested that Marx’s contributions to the critique of political economy can be enhanced by articulating them with the work of two later critical theorists, namely, Antonio Gramsci and Michel Foucault. Accordingly, this article stages an encounter between Marx, Gramsci and Foucault to explore the interface between the semiotic and extra-semiotic aspects of social relations and then identifies four modes of selectivity as a heuristic tool for examining the production of hegemony and the remaking of social relations.
Keywords: Cultural Political Economy; Marx; Gramsci; Foucault; Selectivity; Discourse